2013
DOI: 10.1139/apnm-2012-0115
|View full text |Cite
|
Sign up to set email alerts
|

Objectively measured physical activity levels of children and adolescents in rural South Africa: High volume of physical activity at low intensity

Abstract: There is limited evidence on objectively measured physical activity from Africa. This study quantified physical activity by accelerometry in rural South African children at ages 7, 11, and 15 years. Total physical activity was generally high (mean accelerometer counts per minute ranged 485-1017 across the 3 groups), but moderate- to vigorous-intensity physical activity was low: <1% of the sample met international recommendations. A low intensity, high volume of physical activity is present in rural South Afric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
29
4
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 24 publications
9
29
4
1
Order By: Relevance
“…It is possible that this result is related to lifestyle changes observed in Mozambique during the last decades, mostly due to the urbanization process, which lead to a decrease in leisure time activities linked with increments in electronic entertainment media use among youth as previously suggested 39,40 ; as a result, children became less active and more sedentary 16 ; however, because we do not have any objective information regarding this issue, we can only speculate about this possible association. In addition, there seems to exist a trend among African children and adolescents to be engaged in greater amounts of LPA as compared to MVPA 15,32,41 , although there were no differences in LPA observed in this study. On the other hand, a greater involvement of Portuguese children and adolescents in sports may also explain these results, since their sports practice gives them opportunities for engagement in more energy-demanding activities 15 .…”
contrasting
confidence: 73%
“…It is possible that this result is related to lifestyle changes observed in Mozambique during the last decades, mostly due to the urbanization process, which lead to a decrease in leisure time activities linked with increments in electronic entertainment media use among youth as previously suggested 39,40 ; as a result, children became less active and more sedentary 16 ; however, because we do not have any objective information regarding this issue, we can only speculate about this possible association. In addition, there seems to exist a trend among African children and adolescents to be engaged in greater amounts of LPA as compared to MVPA 15,32,41 , although there were no differences in LPA observed in this study. On the other hand, a greater involvement of Portuguese children and adolescents in sports may also explain these results, since their sports practice gives them opportunities for engagement in more energy-demanding activities 15 .…”
contrasting
confidence: 73%
“…The very high step volumes achieved in the Dikgale sample are in good agreement with the high objectively measured volumes of physical activity in rural black adolescents in another HDSS site. [9] In fact the accelerometrymeasured volumes were nearly three times higher than those for adolescents in the UK, [9] and Dikgale sample achieved average daily step counts more than 1.5 times higher than those reported for North American children and adolescents. [8] OW-OB adolescents often accrued some of the highest daily step counts, and there was no clear pattern of consistently lower daily step counts in the OW-OB group (Fig.…”
Section: Resultsmentioning
confidence: 91%
“…5 Anthropometric variables used to classify the study population according to the IOTF cut-offs for thinness and obesity in children indicated that, in the three age groups, girls tend to be 1.2 times more likely to be classified as obese than boys, but no statistical correlation could be established between physical activity and adiposity.…”
Section: Discussionmentioning
confidence: 94%
“…4 Information available on activity levels in low-and middleincome countries indicated high volume at low-intensity activity. 5 However, little is known about the influence of age and gender on physical activity in the children from these countries.…”
Section: Introductionmentioning
confidence: 99%